Synergistic Effect of Alccofine as Partial Replacement of Cement and M-Sand as Sand Substitution in Concrete for the Assessment of Mechanical and Microstructural Properties - R.S. Ravichandran; J.Saravanan; N. VenkataSairam Kumar (Journal of Sustainable Construction Materials and Technologies, 2025)
Using supplementary cementitious materials (SCMs) and traditional binder mass has revolutionized concrete pro duction technology in the building industry. This study examines how Alcofine-1203 affects the microstructure and mechanical characteristics of concrete. The mechanical qualities of the mixtures were evaluated using six different mixes prepared for each M25 and M40 Grade. In the proposed mixes, cement is substituted with alccofine at 0 to 25% and M-Sand as fine aggregate. The Compressive strength and ultrasonic pulse velocity were assessed after 3, 7, 14, 28, 56, and 90 days of curing, and split tensile strength and flexure strength were evaluated after 28 and 90 days of curing. The samples prepared for SEM, EDS, and XRD tests were carried out to investigate the microstructure of the concrete matrix of M25 and M40 mixes after 28 days of curing. At the replacement level of AF20%, the 28-day compressive, split tensile, and flexural strength for M25 and M40 mixes are recorded as 40.44 MPaand61.65MPa,3.18MPaand5.38MPa, 4.93 MPa and 7.25 MPa, respectively. The quality of concrete is excellent for the replacement levels of M25-AF% and M40-AF% mixes.XRD analysis revealed a high concentration of Anorhitite, Portlandite, and Quartz peaks. Concrete mixes containing 20% alccofine exhibited a more compact, resilient matrix and dense C-S-H gel formation, which is responsible for the improvement in strength properties of the mixes, was observed using scanning electron microscopy and energy dispersive spectroscopy (EDS).